Smart-Access Community Information System - Ababa-En, Meichee B.; Jacildone, Kevin Christopher D.; Killase, Shelly Mae A.; Mantias, Judith S.; Mauricio, Marc Zedric F.; Ruiz, Romeo C.; Felix, Engr. Criselda S. (Future Science / FSH-PH Publications, 2025)
This research study looked into the prospective implementation of the Smart-Access Community Information System (SACIS). The respondents comprised 20 licensed local geodetic engineers who are duly registered with the Geodetic Engineers of the Philippines (GEP), as well as 30 Geodetic Engineering students from Baguio Central School. The study utilized a developmental-descriptive research design in conjunction with a descriptive survey approach to obtain comprehensive insights into stakeholder perceptions. Data were primarily collected through a structured questionnaire, which was carefully adapted and refined to ensure its validity, clarity, and appropriateness for addressing the research objectives. Based on the data collected, the study revealed several key findings: The current level of awareness regarding Smart Access to Land Information was assessed and established. Findings indicate that the Smart-Access platform is highly effective in terms of accessibility, accuracy, efficiency, and transparency. Moreover, the potential challenges that may arise during the future implementation of the Smart Access Community Information System (SACIS) are perceived as very much serious by the respondents, underscoring the need for careful planning and mitigation strategies to ensure successful deployment. The study concludes that the community has moderate awareness of Smart Access Community Information System (SACIS), understanding its objectives and benefits but showing varied knowledge across its purpose, services, and impact. The Smart-Access platform is considered highly effective, improving accessibility, accuracy, efficiency, and transparency compared to traditional methods, and is recognized for enhancing service delivery. However, respondents also perceive potential challenges—such as limited digital infrastructure, low digital literacy, and resistance to change.